The effects of stimulant growth hormones on tissue culture of seaweed Kappaphycus alvarezii in vitro - Fadel, Ariyati H; Gerung, Grevo S; Suryati, Emma; Rumengan, Inneke F.M (Universitas Sam Ratulangi, 2013)
In order to anticipate the qualified and sustainable seed requirement for seaweed culture, it is necessary to conduct tissue culture for vegetative cultivation of isolated leaves, bud, and stemin an artificial medium enriched with nutrient and growth regulator. The purpose of this study is to obtain newly grown plant in a big quantity in relatively short period of time, with physiological and morphological properties similar to the stocks. Culture media used were Grund Medium and PES with an addition of a growth regulator, IAA (Indol acetic acid) and BAP (Benzil amino purin). The buds produced were buds with similar properties as the parent. The longest bud (1,851 mm) was obtained in Grund Medium with IAA treatment, while the length of bud in PES medium was only 0.612 mm. The number of buds was highest (10,6) in Grund media with IAA+BAP (1:1) treatment, and 6,82 with IAA treatment in PES media. The survival rate of explants was highest in media enriched with 0.5 mg/L IAA (indol acetic acid). The best media for growing seaweed Kappaphycus alvarezii was Grund Medium© Untuk mengantisipasi kebutuhan bibit yang berkualitas dan tersedia secara kontinyu, diperlukan suatu upaya kultur jaringan untuk perbanyakan tanaman secara vegetatif dengan mengisolasi bagian tanaman seperti daun, mata tunas, serta batang dalam media buatan secara aseptik yang diperkaya dengan nutrien dan zat perangsang tumbuh. Tujuannya untuk mendapatkan tanaman baru dalam jumlah banyak dalam waktu yang relatif singkat, yang mempunyai sifat fisiologi dan morfologis sama dengan tanaman induknya. Media kultur yang digunakan adalah media Grund Medium dan PES dengan penambahan zat perangsang tumbuh yaitu IAA (Indol acetic acid) dan BAP (Benzil amino purin). Tunas yang dihasilkan merupakan anakan yang mempunyai sifat yang sama dengan induknya. Panjang tunas tertinggi dicapai pada media Grund Medium dengan perlakuan IAA (1,851 mm) dan media PES sebesar 0,612 mm. Sedangkan jumlah tunas tertinggi dicapai perlakuan IAA+BAP (1:1) sebesar 10,6 pada media Grund dan perlakuan IAA sebesar 6,82 pada media PES. Untuk tingkat kelangsungan hidup (sintasan) eksplan yang paling baik pada media yang diberikan pupuk IAA (indol acetic acit) dengan kosentrasi 0,5 mg/L. sedangkan media yang baik untuk pertumbuhan rumput laut Kappaphycus alvarezii adalah media Grund Medium©